Druggability analysis and classification of protein tyrosine phosphatase active sites - Ghattas MA; Raslan N; Sadeq A; Al Sorkhy M; Atatreh N (Dove Medical Press, 2016)
Mohammad A Ghattas, Noor Raslan, Asil Sadeq, Mohammad Al Sorkhy, Noor Atatreh College of Pharmacy, Al Ain University of Science and Technology, Al Ain, UAE Abstract: Protein tyrosine phosphatases (PTP) play important roles in the pathogenesis of many diseases. The fact that no PTP inhibitors have reached the market so far has raised many questions about their druggability. In this study, the active sites of 17 PTPs were characterized and assessed for its ability to bind drug-like molecules. Consequently, PTPs were classified according to their druggability scores into four main categories. Only four members showed intermediate to very druggable pocket; interestingly, the rest of them exhibited poor druggability. Particularly focusing on PTP1B, we also demonstrated the influence of several factors on the druggability of PTP active site. For instance, the open conformation showed better druggability than the closed conformation, while the tight-bound water molecules appeared to have minimal effect on the PTP1B druggability. Finally, the allosteric site of PTP1B was found to exhibit superior druggability compared to the catalytic pocket. This analysis can prove useful in the discovery of new PTP inhibitors by assisting researchers in predicting hit rates from high throughput or virtual screening and saving unnecessary cost, time, and efforts via prioritizing PTP targets according to their predicted druggability. Keywords: PTP1B, oral bioavailability, drug-like inhibitors, drug design, active site, allosteric site, MPtpB, CD45, SHP2, YopH